Federal tax-transfer policy and intergovernmental pre-commitment - Marko Koethenbuerger (Center for Economic Studies and ifo Institute (CESifo), 2007)
Federal and state governments often differ in the capacity to pre-commit to expenditure and tax policy. Whether the implied sequence of public decisions has any efficiency implications is the subject of this paper. We resort to a setting which contrary to most of the literature does not exhibit a perfect tax-base overlap. We show that a federal government's pre-commitment capacity is welfare-improving. Efficiency, however, does not improve over all decision margins. The welfare-increasing policy entails a more distorted level of public consumption. Moreover, welfare may also improve if local governments are able to pre-commit towards the upper level. The rationale is that although federal transfers are formally unconditional they nevertheless entail a tax-price effect; thereby potentially counteracting incentives to engage in a race to the bottom in fiscal competition among local governments.
Keywords: H71; H23; H10; 330; Finanzföderalismus; Finanzausgleich; Steuerpolitik; Steuerwettbewerb; Agency Theory; Theorie